Arde Chicago : misterio en el Condado de Cook - Carter, Charlotte (Charlotte C.) (Nuevos tiempos (Madrid, Spain), 2012)
In 1968, Woodson and Ivy Lisle, an older African-American couple, join forces with their college student grandniece, Cassandra, to investigate the disappearance of the granddaughter of an old family friend.